PENGARUH AUDIT FIRM SIZE, COMPANY SIZE, COMPANY RISK, DAN PROFITABILITY TERHADAP AUDIT FEE - Richelly Gwendella; Catheryn Iona Nelson (Sampoerna University, 2025)
Companies in the Basic Materials sector face increasing demand for audit transparency, making it essential to understand the determinants of audit fees. Strategic factors such as the characteristics of the audit firm and the company itself have been widely acknowledged as crucial elements influencing audit pricing. This study examined the effect of Audit Firm Size, Company Size, Company Risk, and Profitability on Audit Fee among Basic Materials companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period, adopting a quantitative approach. Secondary data were obtained from audited annual reports available on the IDX and official company websites. Using purposive sampling, a total of 42 companies over three years generated 126 observations. Multiple linear regression analysis was conducted using SPSS version 31, supported by descriptive statistics, classical assumption tests, the coefficient of determination test, the F-test, and the t-test. The results indicate that Audit Firm Size and Company Size significantly affect Audit Fee, while Company Risk and Profitability do not show a significant influence. Hence, the study recommends that company management consider the structure and scale of both audit firms and companies when estimating audit costs. Future researchers are encouraged to incorporate additional variables such as firm complexity and audit tenure, which may further explain variations in audit fees.